2021
DOI: 10.1080/10872981.2021.1912879
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of letters to the editor by medical students in medical education journals

Abstract: Letters to the Editor offer ways for readers to engage with authors' publications. Letters are the shortest manuscript for medical students to publish and medical-education journals are best suited. The UK Foundation Programme rewards medical students achieving PubMed ID publications and we hypothesise that this is a main motivation for medical students to submit Letters to the Editor. A review of 15 medical-education journals with an impact factor was conducted to identify numbers and percentages of Letters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Lo anterior, es propio de las dificultades en el contacto con un mentor experto en aspectos metodológicos y de la construcción del conocimiento propio del estudiante en su crecimiento intelectual. La carta al editor, a su vez, otorga mayor oportunidad de publicar un manuscrito en una revista ubicada en los más altos cuartiles, dependiendo de la calidad de la información incluida (puesto que en algunas ocasiones es permitido hacer análisis estadísticos y gráficos sencillos en esta tipología, lo cual da mayor soporte a lo discutido), y, por tanto, mayor oportunidad de ser citado (11). Entonces, se debe incentivar al estudiante a usar herramientas que contribuyan a su formación científica, a la interacción con la evidencia en medicina y los tópicos de mayor relevancia en disciplinas de interés, y que a su vez puedan ayudar a materializar ideas de investigación.…”
Section: Señor Editorunclassified
“…Lo anterior, es propio de las dificultades en el contacto con un mentor experto en aspectos metodológicos y de la construcción del conocimiento propio del estudiante en su crecimiento intelectual. La carta al editor, a su vez, otorga mayor oportunidad de publicar un manuscrito en una revista ubicada en los más altos cuartiles, dependiendo de la calidad de la información incluida (puesto que en algunas ocasiones es permitido hacer análisis estadísticos y gráficos sencillos en esta tipología, lo cual da mayor soporte a lo discutido), y, por tanto, mayor oportunidad de ser citado (11). Entonces, se debe incentivar al estudiante a usar herramientas que contribuyan a su formación científica, a la interacción con la evidencia en medicina y los tópicos de mayor relevancia en disciplinas de interés, y que a su vez puedan ayudar a materializar ideas de investigación.…”
Section: Señor Editorunclassified
“…Letters to the editor can be a valuable venue for academic debate (Teixeira da Silva, 2021) but may also be misused. Gasparyan et al (2016) relay, for instance, the case of an author who published hundreds of editorials and pointless letters presumably to boost publication numbers, while Mukhammadaminov et al (2021) found evidence that U.K. medical students have been submitting unusually high numbers of letters to the editor to increase their publications.…”
Section: Introductionmentioning
confidence: 99%